EFFECTS OF BLOCKCHAIN TECHNOLOGY ON PERFORMANCE OF FINANCIAL MARKETS IN KENYA - Aketch, Sarah; Mwambia, Felix; Baimwera, Bernard (International Journal of Finance and Accounting, 2021)
Purpose: The study sought to establish the effects of blockchain technology on the performance of financial markets in Kenya. Methodology: The study adopted an explanatory research design. The study target population was drawn from the commercial banks located in Nairobi County, Kenya. The study targeted 84 bank managers in the IT and finance department of the 42 commercial banks in Kenya. Thus the target population of the study was 84 financial market managers selected. The study population was grouped into simple identifiable group called strata and adopted a stratified simple random sampling technique with inclusion of commercial banks. A sample size of a sample size of 50 respondents was arrived at. Data was collected using a structured questionnaire. The data collected was cleaned and coded, quantified and analyzed quantitatively. Quantitative data were analyzed using SPSS 24 where descriptive and inferential statistics were used to capture the data in order to understand the pattern and nature of relationships. Results were presented using tables. Findings: The study findings showed that the correlation analysis showed that the adoption of blockchain technology had a positive and significant correlation to government policy R = 0.240. Adoption of blockchain technology had a positive and significant correlation to internet infrastructure by R = 0.293. Adoption of blockchain technology had a positive and significant correlation to transaction cost at R = 0.583. Lastly, adoption of blockchain technology had a positive and significant correlation to risk analysis at R = 0.507. Unique contribution to theory, practice and policy: The study recommended that there should be policy review on issues relating to risk analysis so as to curb illegal money transfers and enhance performance of financial markets in Kenya. The study recommends for a thorough scrutiny by the government and ensures such issues are keenly analyzed to help bring peace and stability in the world. The aspect of having good internet connectivity is beneficial to the nation in that access to proper information will be available and it enables many users to have wide access to services as well as creation of employment. There is need to conduct a study on stability of blockchain technologies use and their impact to the economic growth. The study incorporated Technology Acceptance Model and Innovation Diffusion Theory to link the study topic to the concepts